Desarrollo de destrezas didácticas en el área de lógica-matemáticas en los estudiantes de cuarto grado de educación general básica de la escuela Zulima Vaca Rivera de Pasaje 2014 - 2015. - Morocho Ordoñez, Judy Maribel (2015)
The teaching skills in the area of Mathematical Logic allow develop critical and reflective thinking of students through solving mathematical problems through the application of methods , strategies and innovative techniques , resulting in a process of teaching and learning quality .